Cardiovascular-related health behaviors and lifestyle during the COVID-19 pandemic: An infodemiology study - Omar Dzaye; Siegfried Adelhoefer; Ellen Boakye; Michael J. Blaha (Elsevier, 2021)
Background: Reports have suggested decreasing attention to CVD comorbidities during the COVID-19 pandemic, despite their association with worse virus-related outcomes. Using nowcasting tools, we sought to explore temporal trends in public interest by studying use of online search terms related to CVD comorbidities during the pandemic time period. Methods: We queried Google Trends for recent (October 2019-October 2020) and seasonal (October 2016-October 2020) trends of search terms pertaining to cardiovascular-related behaviors or clinical care including clinical diagnostic and therapeutic-related terms. Additionally, we acquired data from Google Shopping Insights to explore consumer behavior. Data for search results in the US were compared using mean relative search volumes (RSV), tabulated by month. Results: Online search interest in the terms "Exercise" and "Cigarettes" changed by +18.0% and −52.5%, respectively, comparing March-April with January-February 2020. Key terms related to CVD-related care, including diagnostic and therapeutic-related terms such as "Statin", "Lipid profile", "Low-density lipoprotein", and "Hemoglobin A1C" declined to a four-year low in late March 2020 but regained pre-pandemic search query frequency by July 2020. Results were supported by Google Shopping analysis; for example, online consumer shopping-related searches for tobacco products reached at an all-year low after May 2020. Conclusion: We report an increase in search interest for an overall healthier CVD-related lifestyle starting in March 2020, supported by online consumer shopping behavior. However, a months-long trough in public interest for CVD care-related search terms from March-May 2020 suggests a transient but substantial decrease in public focus on cardiovascular-related healthcare engagement. Future research is needed to understand if these mixed signals will persist into 2021 and how they potentially translate into real-world CVD-related event rates.